Network Planning for Haldia Docks Project - Planning Commission, Government of India (Planning Commission, Government of India, 1965)
The Haldia Docks Project Network Planning Report outlines the strategic planning methods employed during the initial phases of the Haldia dock construction to address increasing port traffic and navigational challenges at Calcutta Port. The report emphasizes the creation of a master control network, which provided a comprehensive overview of project activities, identified critical tasks, and facilitated efficient resource allocation. This master network enabled accurate forecasting of project timelines and financial planning, while detailed networks for specific components ensured smooth operational execution. The planning approach, incorporating work breakdown, milestone setting, and critical path analysis, enhanced coordination among multiple stakeholders and improved decision-making processes. The methodology highlights the significance of systematic network planning in achieving timely project completion and effective management of complex infrastructure projects.
Committee on Plan Projects, Planning Commission, Government of India
Committee on Plan Projects, Planning Commission, Government of India
Keywords: Haldia Docks Project; Network Planning; Master Control Network; Critical Path Analysis; Project Management; Port Infrastructure; Resource Allocation; Project Coordination; Timeline Forecasting; Calcutta Port